2021
DOI: 10.3389/fimmu.2020.578715
|View full text |Cite
|
Sign up to set email alerts
|

Process Development of Sj-p80: A Low-Cost Transmission-Blocking Veterinary Vaccine for Asiatic Schistosomiasis

Abstract: Asiatic schistosomiasis caused by Schistosoma japonicum is a neglected tropical disease resulting in significant morbidity to both humans and animals - particularly bovines - in endemic areas. Infection with this parasite leads to less healthy herds, causing problems in communities which rely on bovines for farming, milk and meat production. Additionally, excretion of parasite eggs in feces perpetuates the life cycle and can lead to human infection. We endeavored to develop a minimally purified, inexpensive, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…In a different immunization study with Sj-p80 in Montanide TM ISA61VG adjuvant carried out in mice infected with Schistosoma japonicum, there was a reduction in the female burden, but the number of eggs did not decrease. However, the viability/hatching rates of the eggs were reduced [34]. A vaccination system using the 14-3-3 protein from Schistosoma bovis and FABP from Fasciola hepatica yielded high protection in terms of parasite burden and liver damage [19,22].…”
Section: Discussionmentioning
confidence: 99%
“…In a different immunization study with Sj-p80 in Montanide TM ISA61VG adjuvant carried out in mice infected with Schistosoma japonicum, there was a reduction in the female burden, but the number of eggs did not decrease. However, the viability/hatching rates of the eggs were reduced [34]. A vaccination system using the 14-3-3 protein from Schistosoma bovis and FABP from Fasciola hepatica yielded high protection in terms of parasite burden and liver damage [19,22].…”
Section: Discussionmentioning
confidence: 99%
“…Montanide ISAs (Incomplete Seppic adjuvants) similar to IFA are shown to induce strong cytotoxic Tlymphocyte (CTL) responses and long-term immunity with minimal side effects and are also stable and easy to inject [94]. Some vaccines that use Montanide ISA as adjuvants include S. japonicum insulin receptors, Calpain, and paramyosin [104][105][106].…”
Section: The Role Of Adjuvants In the Development Of Schistosomiasis ...mentioning
confidence: 99%
“…Not surprisingly, the cross-reactivity of S. mansoni calpain (Smp80) was tested against S. japonicum infection in mice, resulting in a 47% reduction in worm burden [183,184]. Subsequently, a pilot study demonstrated the practicality of purifying recombinant S. japonicum calpain (Sj-p80) as a veterinary vaccine, resulting in protection against infection in mice with robust antibody titres and a reduction of eggs deposited in the liver (up to 51%) [105]. S. japonicum Glyceraldehyde dehydrogenase (SjGAPDH) is a glycolytic enzyme important for the energy provision needed for the growth of the schistosomula [190].…”
Section: S Japonicum Calpains (Sj-p80)mentioning
confidence: 99%
“…It shows no immunological cross-reactivity with calpains in vertebrates; Sm-p80 is expressed in all schistosome lifecycle stages though with a 2.5-fold higher expression in females compared to male adult worms, and plays a pivotal role in membranous biosynthesis and turnover (116)(117)(118)(119)(120)(121)(122)(123). Sm-p80 induced cross-species protection against Sh with reductions of 48% worms, and 66% and 63% hepatic and intestine eggs in Syrian hamsters, respectively, and reductions of 25% worms, and 64% urinary bladder, 40% fecal and 53% urinary eggs in Papio anubis baboons with robust immune responses indicative of balanced Th1/Th17 immunity though slightly biased to a Th2 response (125,126). Cross-species protection was also shown against Sj using GLA-SE-adjuvanted Sm-p80, and against Sh using a Sm-p80-VR1020 DNA prime and CpG-ODNadjuvanted protein boost approach with reductions of 47% of worms and 5% of hepatic eggs in mice, and reductions of 27% worms but no effects on hepatic, intestinal and urinary eggs in hamsters, respectively, and a balanced Th1/Th2 immune response (122,126).…”
Section: S Mansoni Large-subunit Calpainmentioning
confidence: 99%
“…Following vaccination of baboons with Sm-p80 with GLA-SE, egg levels were reduced in liver (91%), small intestine (87%), and large intestine (91%). Female adult worms and egg hatching into miracidia decreased by 93% and 82%, respectively (123,126). The retention of some non-pathogenic male worms of stunted growth and shorter life spans due to lack of pairing in the absence of female worms may be of benefit in recurrent boosting of the natural immunity and resistance to schistosomiasis.…”
Section: S Mansoni Large-subunit Calpainmentioning
confidence: 99%